Effects of Drug Testing on Defendant Risk in Dade County, Florida, 1987 - Goldkamp, John S. ([Verlag nicht ermittelbar], 1992)
The purpose of this data collection was to explore the relationship between drug use and crime. Specifically, the collection was undertaken to determine whether drug test results could provide important predictive information on pretrial misconduct over and above that provided by other variables, thus supplying more data for judges to use in making bail and pretrial release decisions. Data about defendants and their criminal and drug use history were gathered. In addition, defendants were subjected to urinalysis drug testing procedures to determine the presence or absence of drugs in the urine. Both the drug testing methods and subsequent results were subjected to reliability and validity testing procedures. The independent variables in the study include demographic attributes such as defendant's sex, race, birthdate, marital status, and employment, charge-related attributes such as current offense, arrest, and court disposition, prior criminal record of the defendant, current and past drug use, and drug testing results. The dependent variables pertain to the defendant's pretrial performance and include items such as failure to appear and any rearrests.